2009
DOI: 10.1002/pssb.200945489
|View full text |Cite
|
Sign up to set email alerts
|

Resonant tunnelling in a Fibonacci bilayer graphene superlattice

Abstract: The transmission coefficients (TCs) and angularly averaged conductance for quasi-particle transport are studied for a bilayer graphene superlattice arranged according to the Fibonacci sequence. The transmission is found to be symmetric around the superlattice growth direction and highly sensitive to the direction of the quasi-particle incidence. The transmission spectra are fragmented and appear in groups due to the quasiperiodicity of the system. The average conductance shows interesting structures sharply de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Motivated by the experimental realization of graphene superlattice (GSL) [10][11][12], electronic bandgap structures and transport properties in GSLs with electrostatic potential and magnetic barrier have been extensively investigated [13][14][15][16][17][18][19][20][21][22], since the conventional semiconductor superlattices are successful in controlling the electronic structures and the extension to graphene may give rise to different features and applications. For instance, DP appears in the GSL [14,15], and it is exactly located at the energy with the zero-k gap [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the experimental realization of graphene superlattice (GSL) [10][11][12], electronic bandgap structures and transport properties in GSLs with electrostatic potential and magnetic barrier have been extensively investigated [13][14][15][16][17][18][19][20][21][22], since the conventional semiconductor superlattices are successful in controlling the electronic structures and the extension to graphene may give rise to different features and applications. For instance, DP appears in the GSL [14,15], and it is exactly located at the energy with the zero-k gap [17].…”
mentioning
confidence: 99%
“…As we know, the quasi-periodic GSL is classified as intermediate between ordered and disordered systems [19,20], which has significant and common features like fractal spectrum and self-similar behavior [21,22]. How- * Corresponding author.…”
mentioning
confidence: 99%
“…All these studies focus primarily on monolayer graphene, and the preferred mechanism to create the quasi-periodic pattern has been the electrostatic field effect. So far, the quasi-periodic patterns studied in graphene have been Cantor [33][34][35], Fibonacci [36][37][38][39][40], Thue-Morse [41][42][43][44][45][46][47], Double-Period [48] and Gaussian [49,50]. One of the most remarkable characteristics of quasi-periodic patterns in graphene, regardless of the quasi-periodic sequence used, is a zero-gap associated to an unusual Dirac point.…”
Section: Introductionmentioning
confidence: 99%
“…So, by considering the importance of the quasi-periodic modulation, from both the fundamental and technological standpoints, it seems natural that it be an extension for any novel material. To this respect graphene is not the exception, and in the last years the interest in aperiodic or quasi-periodic modulation in graphene is rising [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. All these studies focus primarily on monolayer graphene, and the preferred mechanism to create the quasi-periodic pattern has been the electrostatic field effect.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the transmission coefficient and the angularly averaged conductance in a Fibonacci BG superlattice have been investigated in detail. 22 It is shown that the transmission spectra are fragmented and appear in groups due to the quasi-periodicity of the system. Using the four-band Hamiltonian as well as the two-band Hamiltonian, Barbier et al 23 have studied the dispersion relation and the density of states in a BG superlattice with a periodic potential applied to the both layers and found that the dispersion relation shows a finite gap for carriers with zero momentum in the direction parallel to the barriers.…”
mentioning
confidence: 99%